Phylogeographical history of the Olive Woodpecker Dendropicos griseocephalus, a species widely distributed across Africa. (11th October 2020) - Fuchs, Jérôme; Bowie, Rauri C. K.; Melo, Martim; Boano, Giovanni; Pavia, Marco; Fjeldså, Jon
Abstract : Few studies have quantified the extent of genetic differentiation within widely distributed polytypic African bird species with disjunct ranges. Current knowledge indicates that high levels of genetic differentiation are found for such lineages but generalization of the pattern requires further comparisons with other co‐distributed taxa. We assessed the extent of phylogeographical structure across the range of the Olive Woodpecker Dendropicos griseocephalus using mitochondrial and nuclear intron data. The Olive Woodpecker occupies the forests of Central ( Dendropicos griseocephalus ruwenzori ) and Eastern ( Dendropicos g. kilimensis ) Africa, with a disjunct morphological lineage ( Dendropicos g. griseocephalus ) occurring in southern Africa. Each of the subspecies lineages can be diagnosed using morphology. Phylogenetic analyses of our sequence data recovered three monophyletic lineages with kilimensis sister to ruwenzori, and griseocephalus as sister to the clade uniting these two taxa. Molecular species delimitation methods and estimates of gene flow under the isolation‐with‐migration model suggest that the clade uniting the central and eastern subspecies may be recognized as distinct at the species level from the nominate subspecies, which is restricted to southern Africa. We conclude that D. griseocephalus (Boddaert, 1783) and D. ruwenzori (Sharpe, 1902) (including subspecies kilimensis ) should be considered full species. The biogeographical pattern we uncover for the Olive Woodpecker differs from that of other co‐distributed widespread species both in terms of the order of sequence divergence of lineages occupying different areas of endemism in Africa, and in the timing of divergence, being younger (0.5–0.7 mya BP) than that recovered for the co‐distributed Square‐tailed Drongo Dicrurus ludwigii (0.9–1.6 mya BP).